Assessment of Right Atrium Function in Patients With Systemic Lupus Erythematosus With Different Pulmonary Artery Systolic Pressures by 2‐Dimensional Speckle‐Tracking Echocardiography. (26th February 2018) - Sun, Lihua; Wang, Ying; Dong, Yu; Song, Shengda; Luo, Runlan; Li, Guangsen
Abstract : Objectives: To assess right atrium (RA) function of patients with systemic lupus erythematosus (SLE) and pulmonary artery hypertension (PAH) by 2‐dimensional speckle‐tracking echocardiography. Methods: Thirty matched healthy adults were selected as group A. Then, 102 patients with SLE were divided into 3 groups according to the severity of PAH. Group B included 37 patients without PAH (pulmonary artery [PA] systolic pressure ≤ 30 mm Hg); group C included 34 patients with PAH (PA systolic pressure of 30–50 mm Hg); and group D included 31 patients with PAH (PA systolic pressure ≥ 50 mm Hg). Parameters evaluated included RA maximum volume, minimum volume, preatrial contraction volume, passive ejection fraction (EF), and active EF. The global peak longitudinal systolic strain rate and early and late diastolic strain rates of the RA were obtained by 2‐dimensional speckle‐tracking echocardiography. Results: No significant differences were found in all parameters between groups B and A ( P  > .05). The RA maximum volume, minimum volume, preatrial contraction volume, active EF, and late diastolic strain rate in groups C and D were significantly increased compared with those in groups A and B, and the parameters in group D were significantly higher than those in group C ( P  < .05). Although the RA passive EF, early diastolic strain rate, and systolic strain rate in groups C and D were significantly decreased compared with those in groups A and B, those in group D were significantly lower than those in group C ( P  < .05). Conclusions: Two‐dimensional speckle‐tracking echocardiography could effectively assess RA function in patients with SLE who have different severities of PAH.